PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN LENSA KACAMATA MEREK DOMAS PADA PT. DUTAMULTI INTIOPTIC PRATAMA MEDAN - Ina Namora Putri Siregar; Susan Susan (Jurnal PLANS : Penelitian Ilmu Manajemen dan Bisnis, 2018)
High purchasing decisions from consumers of a product is the most important aspect for a company in doing business activity. To increase high purchases from consumers, companies should take account of the factors that influence purchasing decisions; one of them is product quality and promotion provided by the company. The purpose of this study is to examine and analyze the effect of product quality and promotion on purchasing decisions of the lens eyewear brand Domas at PT. Dutamulti Intioptic Pratama Medan. This research uses theories about product quality, promotion and purchasing decisions. This research uses quantitative approach, this type of research is descriptive quantitative and the nature of this research is explanatory. Data collection was done through interviews and questionnaires. Method of data analysis of this study is multiple linear regression. The population of this study is 100 customers who make regular purchases at PT. Dutamulti Intioptic Pratama. The results of this study show that partially the quality of calculation products showed that T-count 4,886> T-table 1.99 and promotion with T-count 8,785> T-table 1.99 have a positive and significant effect on purchasing decision. Simultaneously, the value of product quality and promotion showed F-count 72,842 > F-table 2.74 have a positive and significant effect on the lens of Domas brand eyewear at PT. Dutamulti Intioptic Pratama Medan. The conclusion of the study states that partially and simultaneously the qualities of products and promotions have a positive and significant effect on purchasing decisions of Domas eyewear lens at PT. Dutamulti Intioptic Pratama Medan. Keywords: Product Quality, Promotion, Purchase Decision